Analysis of the Influence of Financial Performance Factors Before and After Mergers and Acquisitions - Amin Wijoyo; Steven Wiryajaya; Cordelia Stella Chandra (Institute for Law and Economics Studies, 2026)
This research seeks to provide empirical evidence on changes in banking financial performance before and after mergers and acquisitions (M&A). Performance is assessed using several commonly applied financial ratios in the banking sector, namely Capital Adequacy Ratio (CAR), Return on Assets (ROA), Return on Equity (ROE), Non‑Performing Loans (NPL), Operating Expenses to Operating Income (BOPO), Loan to Deposit Ratio (LDR), and Total Asset Turnover (TATO). These indicators were selected because they capture diverse aspects of asset utilization within banks. This research population includes banks registered on the Indonesia Stock Exchange (IDX) during the 2011–2024 period that were involved in mergers and acquisitions. Using purposive sampling, 11 institutions met the criteria. Secondary data from annual reports were analyzed, with initial calculations performed in Microsoft Excel and further statistical testing conducted in SPSS. Depending on the normality results, differences were examined using either the paired sample t‑test or the Wilcoxon signed‑rank test. The findings are expected to contribute both academically and practically by evaluating the effectiveness of M&A strategies in enhancing the performance of Indonesian banks